THE PSYCHOLOGICAL STRESS LEVEL IN MONGOLIAN PEOPLE QUARANTINED DURING THE COVID-19 OUTBREAK - Purevdor, Dulamjav; Khusman, Oyungerel; Sodnomdash, Baigalmaa; Baatar, Bayasgalanmunkh; Kokhan, Sergey; Razumova, Elena (Revista Inclusiones, 2020)
The WHO has identified Mongolia as one of the countries with the highest risk of infection. All registered cases of coronavirus infection in Mongolia were imported from abroad. In Mongolia, all visitors who entered from countries with foci of COVID-19 infection were assigned 21-days of quarantine. Our principal aim was to investigate the stress levels in people who are in quarantine of COVID-19 infection using a PSM-25 scale. Our secondary aim was to determine the needs of respondents for psychological assistance. Methods: The 130 respondents of the study, who crossed the Mongolian border and were in 21 days quarantine during COVID-19 infection, were asked to fill out the psychological stress scale (PSM-25).The assessment of the internal consistency of the original stigma questionnaire was performed by using Cronbach's α=0.71. When we assessed the stress levels, the respondents identified with 42.9% low, 53.7% averge and 10.7% high stress levels. The study determined that the most urgent, frequently repeated psychological questions among the respondents are 47.6%, feeling of anxiety 33.1%, insomnia 22.3% emotional imbalance, impaired attention concentration, feeling of loneliness and 6.9% constant anxiety.The 10.7% ofthe quarantined respondents during COVID-19 infection in Darkhan have a high stress level. To overcome these problems, relieve stress and create a feeling of comfortability, people in quarantine need psychological care.